Determination of current homogeneity on the electrodes of lead-acid batteries through electrochemical impedance spectroscopy. (10th October 2019) - Calborean, Adrian; Murariu, Teodora; Morari, Cristian
Abstract: This work explores a qualitative appraisal of lead acid battery electrodes by Electrochemical Impedance Spectroscopy. Lead acid cells behavior has been examined by gathering data of impedance modifications in distinct electrolyte volumes, from a full one to a battery filled at about 20% of the total volume of acid. Since the current between electrodes is inhomogeneous around the collector by varying the quantity of the electrolyte, we have associated numerical values of the elements in the battery equivalent circuit, to the homogeneity of the current in the electrodes. Theoretical considerations dealing with modeling, equivalent circuits and corresponding equations are provided. As a function of the electrolyte quantity, we investigated the dependence of the values for components of the Randle circuit. A particular attention has been devoted to constant phase element (CPE) peculiarities, as this parameter was found essential for a good quality fit over an extended range of batteries. The stability depending on current homogeneity at a certain battery state of charge was analysed in order to assess the effect of electrolyte volumes, and thereby to provide new quality requirements for improvement of lead-acid battery performance.